2022
DOI: 10.2166/ws.2022.333
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dike systems on hydrological regime in Vietnamese Mekong Delta

Abstract: This paper examines the impact of the dike systems on river flows in the Vietnamese Mekong Delta (VMD). The study combined a hydrological change index method and the Mann-Kendall test to assess the temporal dynamics of both discharge and water levels along the main rivers of the VMD. Results highlight that the system of rivers and canals helps facilitate waterway traffic and drainage during the flood season. However, the low elevation of the delta has created conditions suitable for saline water to increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The flood season in the Mekong Delta commences in June and July, concludes in November and December, and is followed by a 6-month dry season. The hydrological regime of the Mekong Delta has been impacted by various factors, such as climate change, land use changes, and the construction of hydropower infrastructure (Orieschnig et al, 2023), (Xuan et al, 2022). These changes have led to shifts in the timing, duration, and spatial distribution of annual monsoon inundations in the delta (Orieschnig, Belaud, et al, 2022).…”
Section: Figure 1 the Geographical Location And Metrological Stations...mentioning
confidence: 99%
“…The flood season in the Mekong Delta commences in June and July, concludes in November and December, and is followed by a 6-month dry season. The hydrological regime of the Mekong Delta has been impacted by various factors, such as climate change, land use changes, and the construction of hydropower infrastructure (Orieschnig et al, 2023), (Xuan et al, 2022). These changes have led to shifts in the timing, duration, and spatial distribution of annual monsoon inundations in the delta (Orieschnig, Belaud, et al, 2022).…”
Section: Figure 1 the Geographical Location And Metrological Stations...mentioning
confidence: 99%
“…Monthly rainfall was collected from 1980 to 2019, and monthly average values of T max , T min , and T ave. , were collected from 2000 to 2019. The Mann-Kendall test was used to evaluate the trend of data collection, SPI, ARI, and SPEI (see references [25][26][27]). The monthly data of T min , T max , and T ave. all slightly increased, while the monthly rainfall was seen to slightly decrease between 2000 and 2019, but not statistically significantly (Figure 1).…”
Section: Data Collection and Trend Analysismentioning
confidence: 99%
“…Firstly, we applied the Mann-Kendall statistical test to detect monotonic trends in data. A large bevy of previous studies have used this statistical test to ascertain the presence of statistically significant trends in meteorological and climatic timeseries datasets [18][19][20][21][22][23]. Furthermore, Sen's slope estimator can yield a trend slope estimate and is comparatively robust to outliers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, innovative trend analysis (ITA) was established to address the shortcomings of the MK test [24,25]. Prior studies have reported that ITA provides reliable results over the MK test to detect trends in climate parameters [19,[26][27][28]. Furthermore, as of late, innovation trend analysis (ITA) has gained popularity [24], as it is capable of capturing nonlinear trends and offers additional insights into the data's structure, including trend identification across all value ranges [29].…”
Section: Introductionmentioning
confidence: 99%